2009
DOI: 10.1007/978-3-642-03549-4_1
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating Inadvertent Insider Threats with Incentives

Abstract: Abstract. Inadvertent insiders are trusted insiders who do not have malicious intent (as with malicious insiders) but do not responsibly managing security. The result is often enabling a malicious outsider to use the privileges of the inattentive insider to implement an insider attack. This risk is as old as conversion of a weak user password into root access, but the term inadvertent insider is recently coined to identify the link between the behavior and the vulnerability. In this paper, we propose to mitiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…Insiders' privileged access allows them to easily abuse organizational trust for personal gain [34]. Privileged access makes it simpler for the insider to cause serious harm to the organization than it would be for someone attacking from outside.…”
Section: Access and Level Of Trustmentioning
confidence: 98%
“…Insiders' privileged access allows them to easily abuse organizational trust for personal gain [34]. Privileged access makes it simpler for the insider to cause serious harm to the organization than it would be for someone attacking from outside.…”
Section: Access and Level Of Trustmentioning
confidence: 98%
“…On the other hand, previous works have designed incentive mechanisms (e.g., [11], [12]) and information mechanisms (e.g., [13]) to enhance insiders' compliance, reduce users' misbehavior, and reduce false positives.…”
Section: A Alert Managementmentioning
confidence: 99%
“…So the system is very secure. Wang and Puleo [9,10] worked on the behavioral aspect of insiders. According to the research conducted, it was found that most of the insiders have one or more of the following observable behavior.…”
Section: IImentioning
confidence: 99%